Is evolution predictable? Quantitative genetics under complex genotype‐phenotype maps. (3rd January 2020) - Milocco, Lisandro; Salazar‐Ciudad, Isaac
Abstract: A fundamental aim of post‐genomic 21st century biology is to understand the genotype–phenotype map (GPM) or how specific genetic variation relates to specific phenotypic variation. Quantitative genetics approximates such maps using linear models, and has developed methods to predict the response to selection in a population. The other major field of research concerned with the GPM, developmental evolutionary biology, or evo‐devo, has found the GPM to be highly nonlinear and complex. Here, we quantify how the predictions of quantitative genetics are affected by a complex, nonlinear map based on the development of a multicellular organ. We compared the predicted change in mean phenotype for a single generation using the multivariate breeder's equation, with the change observed from the model of development. We found that there are frequent disagreements between predicted and observed responses to selection due to the nonlinear nature of the genotype–phenotype map. Our results are a step toward integrating the fields studying the GPM.